ANALISIS PUTUSAN MENERIMA PERMOHONAN PENYELESAIAN HASIL PILKADA SERENTAK DI MAHKAMAH KONSTITUSI (STUDI PERKARA KABUPATEN YALIMO, TAHUN 2020): Analysis Decisions Of Accepting Applications For Settlement Election Results In The Constitutional Court (Yalimo District Case Study, 2020) - Janwardisan Hernandika; Yogo Pamungkas (Faculty of Law, Universitas Trisakti, 2024)
Examines the decision of the Constitutional Court which accepted the request to resolve the results of the simultaneous regional elections. The formulation of the problem is whether the application for a dispute over the results of the regional head election in Yalimo Regency in 2020 is in accordance with statutory regulations and whether the legal considerations of the Constitutional Court judges in accepting the application for a dispute over the results of the simultaneous regional elections in decision number 97/PHP.BUP-XIX/2021 which is not in accordance with Article 158 of the Regional Election Law. The research method is descriptive analytical with secondary data analyzed qualitatively, type of research is normative juridical. The results of research and discussion stated that the dispute over the results of the 2020 regional head election in Yalimo Regency was in accordance with the law, however the submission of the application did not comply with the threshold provisions or the application exceeded the maximum threshold of 2%. The conclusion is the Constitutional Court has strong reasons to continue the examination of the a quo case to the next level and can decide to deviate from the provisions of Article 158 paragraph (2) letter a of Law 10/2016